Legal Theory as the Foundation of Certainty, Justice, and Utility in the Indonesian Judicial System - Suhardi, Somomoeljono (The International Journal of Law Review and State Administration, 2025)
Legal theory plays a fundamental role in shaping both the intellectual framework and the practice of law enforcement in Indonesia. As a normative system, law is not only required to provide certainty but also to ensure justice and deliver practical utility for society. Legal certainty functions as the basis for consistent enforcement of rules, justice represents the moral goal of law, and utility emphasizes the law’s practical value in addressing social needs. This article examines legal theory as the primary foundation of Indonesia’s judicial system, highlighting the debate among legal positivism, natural law theory, and progressive law in achieving a balance between these three fundamental values. The study employs a normative approach with conceptual analysis of various schools of legal thought and their implementation in judicial practice. Findings reveal that the Indonesian judicial system continues to face challenges in harmonizing certainty, justice, and utility particularly in the context of law enforcement oriented toward substantive justice. Thus, reinterpretation and revitalization of legal theory are needed to make it more adaptive to societal developments, while maintaining the supremacy of law as an instrument of social justice.